MDAO method and optimum designs of hybrid-electric civil airliners - Kang, Le; Sun, Yicheng; Smith, Howard (American Society of Civil Engineers (ASCE), 2022)
Hybrid-electric civil airliners (HECAs) are considered the forerunner of the solution of relieving aviation emissions. This paper presents a multidisciplinary design analysis and optimization (MDAO) framework named GENUS, which has been extended to design HECAs. GENUS is a modular, expandable, and flexible design environment with 10 integrated modules for HECA design. Key extensions included hybrid-electric propulsion architectures (HEPAs), the corresponding powertrains, and power management strategies (PMS). In addition, a cost module and an aviation emission tracking function were developed and integrated into GENUS. GENUS was validated for investigating the design of HECAs by evaluating existing HECA concepts. Furthermore, three conventional turbofans were hybridized within GENUS to analyze the sensitivity of the performance of engines to the degree of hybridization (DoH) of power. The effects of hybridized engines on aircraft design were evaluated based on Boeing 737, demonstrating that at least 27.18% fuel saving, 9.97% energy saving, 12.40% cost saving, and 43.56% aviation emissions migration can be achieved. Finally, the potential directions of applying GENUS to explore the design space of HECA was discussed, which is useful to maximize the benefits of HECA.
Keywords: Multidisciplinary design analysis and optimisation (MDAO); hybrid-electric civil airliner (HECA); Fuel-battery hybrid; Conceptual aircraft design